Human embryonic stem cell-derived neural crest model unveils CD55 as a cancer stem cell regulator for therapeutic targeting in MYCN-amplified neuroblastoma. Issue 6 (16th October 2021) - Weng, Zhihui; Lin, Jiacheng; He, Jiaozi; Gao, Lin; Lin, Sien; Tsang, Lai Ling; Zhang, Hang; He, Xiaoyan; Wang, Guang; Yang, Xuesong; Zhou, Hu; Zhao, Hui; et al.
Abstract: Background: Neuroblastoma (NB) is a common childhood malignant tumor of neural crest (NC) origin with remarkable heterogeneity in outcomes. Amplification of the oncogene MYCN is strongly associated with highly malignant behaviour and poor prognosis. Methods: This study aims to use a human embryonic stem cell (hESC)-derived NC model to identify novel downstream effectors of MYCN that can be potentially used as prognostic marker and/or therapeutic target. Results: We show that MYCN-driven NB derived from human neural crest cells (hNCCs) recapitulate the pathological and molecular features of MYCN -amplified neuroblastoma (MNA-NB). By using this platform, we identify a group of 14 surface protein-encoding genes that are associated with MYCN expression level in MNA-NB. Among these genes, high CD55 expression is correlated with poor survival in MNA-NB but not in non-MNA-NB. Furthermore, CD55 promotes tumorigenesis, tumor growth, and cancer stemness in MNA-NB cell lines (MNA-NBL) through regulating the JNK pathway. Mechanistically, MYCN binds to both canonical and noncanonical E-boxes on the promoter of CD55 to regulate its transcriptional expression. Finally, neutralizing antibody targeting CD55 significantly attenuates cancer stemness, suppresses tumor growth, and improves survival exclusively in MNA-NBL-inoculated mice. Conclusion: MYCN shapes CD55 into a cancer stem cell regulator which represents a prognostic marker and therapeutic target of MNA-NB. The hESC-derived NC model serves as a valuable platform for investigating NB initiation and progression and developing potential therapeutic targets.